A wolf in dog's clothing: Initial dog domestication and Pleistocene wolf variation. (April 2016) - Perri, Angela
Abstract: The process and timing of initial dog domestication is an important topic in human evolution and one which has inspired much recent debate. Findings of putative domesticated dogs have recently been reported from two Gravettian sites by Germonpré et al. (2015a), joining a handful of other reputed "Paleolithic dogs" dating to before the Last Glacial Maximum (LGM). Though these findings have been challenged previously, this paper draws attention to the most significant shortcoming in claims of early domesticated dogs – a lack of data on Pleistocene wolf variation. Without comprehensive data on the range of variation within Pleistocene wolf populations, the identification of domesticated dogs from prior to the Late Upper Paleolithic cannot be conclusively accepted or rejected. Highlights: The timing and location of dog domestication is still uncertain. A handful of proposed Paleolithic (pre-16, 000 BP) domesticated dog remains have been reported from Europe and Siberia, but are highly contested. Very little Pleistocene wolf material has been analyzed for comparison to putative Paleolithic dogs. Without comprehensive data on Pleistocene wolf variation, claims for Paleolithic domesticated dogs cannot be conclusively accepted or rejected.